Forage harvesting using branch pruning compromises sustainable use and conservation of Pterocarpus erinaceus Poir., an endangered species - Bossila Séraphin Hien; Loyapin Bondé; Mohamed Mahamoud Charahabil; Sié Sylvestre Da; Joseph Issaka Boussim; Oumarou Ouédraogo (Nature Conservation)
Pterocarpus erinaceus Poir. is a leguminous tree species with huge forage value. It is subjected to heavy pruning pressure in dry season for livestock feeding, resulting in yearly decline of forage production and vulnerability of the species which is currently classified as endangered species. This study aimed at: (i) identifying factors influencing branch pruning pressure on P. erinaceus tree, (ii) assessing the effect of branch pruning on foliage production of the species and (iii) developing allometric equations for estimating its foliage biomass. We measured leaf biomass on representative living branches on 48 individual trees of P. erinaceus distributed in protected and communal areas following topography gradient. Branch size distribution and branch pruning ratio (PR) expressing human pressure on sampled trees were appreciated. Results indicated that PR was significantly (p-value < 0.001) influenced by tree morphological traits such as diameter at breast height (DBH) and crown area, and tree density around sampled tree. Linear regression highlighted the dominance of small branches on sampled trees both for pruned and living branches, suggesting a regular pruning of trees. Topography position and PR were found as main factors affecting the species leaf production (p < 0.05). The potential leaf biomass estimated at 15.09 ± 6.58 kg per tree is reduced by 35.98% when using branch pruning for forage harvesting. DBH and PR were the best predictor variables for estimating leaf production of the species. Allometric model developed is a useful tool for optimizing harvesting activities and secure sustainable use of the species. Based on the harvesting pressure observed on the species, the promotion of more conservative harvesting techniques such as cutting of leafy twigs for forage harvesting instead of branch pruning and preserving of heavy pruned trees from harvesting during few years are highly recommended for enabling fast renewal of branches and seed production for species regeneration. Findings and recommendations from this case study on P. erinaceus could be used to improve the management of tree species subjected to similar harvesting pressure across tropical regions.